Przeobrażenia i realizacja funkcji wydawniczych polskich mediów misyjnych w okresie pandemii covid-19 - Wrzos, Marcin Jan (Annales Missiologici Posnanienses, 2021)
The Polish missionary media of social communication has been appearing since 1882. In the analyzed period, they performed their role very well in the period of the covid-19 pandemic. They quickly reacted to a crisis situation, informing about it fairly and widely, and in some titles it translated into inviting readers to spiritual and material commitment to specific needs. A special tool in this is the media communicating via the Internet, especially social media, which allow for immediate information and reactions to a short- or long-term crisis situation. The study shows that the publishing functions performed by this press include: informational and journalistic, promoting the mission and the missionary idea, catechetical and formation, new evangelization and evangelization, fundraising for the mission, awakening missionary vocations, organizing mission groups, opinion-forming and attitude-forming. It seems that in the main assumptions, the implementation of these functions at the level of ideas has not changed, and the differences result primarily from changes in the communication technique and the diversity of target groups. Before starting the research, the following hypotheses and research theses were formulated, which we then tried to verify (hypotheses) or confirm (theses) in the course of the research. Thesis 1: during the covid-19 pandemic, leading mission journals performed the press functions for which they were created – has been confirmed. Hypothesis 1: the press functions performed by the press media and the media communicating via the Internet differed – it was verified negatively. However, it is noticeable that individual media are used based on their technical capabilities (quick information and immediate help was possible through the media communicating via the Internet) and target groups (Internet users are younger and the content was usually prepared with them in mind). Hypothesis 2: the main functions performed were: information, organization and fundraising – in the field of assistance to the publisher’s legal entity – has been positively verified.